An Unusual Osseous Lesion of Mandibular Condyle - Chaurasia, Akhilanand (Journal of Orofacial Research, 2012)
Peripheral osteomas are rare tumors of jaws arising from proliferation of cancellous or compact bone increasing in size by continuous bone formation. These lesions appears as unilateral, pedunculated or seesile mushroom-like masses, well-marginated and varying in diameter from 10 to 40 mm. The first case of peripheral osteoma involving condylar process was reported by Ivy in 1927. Since then only 13 cases of osteoma arising in condylar process have been reported in literature. Osteoma of condyle is relatively rare and it may cause a slow progressive shift in patient’s occlusion with deviation of the midline of the chin toward unaffected side. Here, a case of peripheral osteoma of mandibular condyle is presented.